El gran circo pobre de Timoteo - Giachino Torréns, Lorena (Errante Producciones, 2013)
"The comedian Timoteo is the leader of a gay cross-dresser circus that has toured through Chile for forty years. Today his advanced age and health are reason for concern regarding the continuity of the show. The cast is worried the Circus will end, and with it, the family they've had for years. Small episodes and daily conflicts shape the comedian's life while he debates between denial of a possible ending and the concrete need to project his circus."--